Enhancing Asia’s trade: price and non-price barriers revisited - Prabir De (Journal of International Logistics and Trade, 2010)
In a supply-constrained region like Asia, promoting exports has always been a challenge particularly at a time when Asia’s trade has been severely affected by lack of external demand. This paper argues that price barriers have taken a new shape during the global financial crisis period which may generate differential impacts on trade flows as we proceed toward recovery. The size and shape of price barriers would be higher if NTBs, applied by the countries during the crisis period, were counted. One of the conclusions of this paper is that ‘price’ barrier is still more important than ‘non-price’ barrier in enhancing Asia’s trade and integration. The higher the price barrier between countries in a pair, the less they trade. In other words, a 10 percent increase in the ad-valorem price (transport and tariff) lowered trade by 6 percent. Tariff and transport costs, each considered separately, also influence the trade flow in the same direction, to more or less the same extent. There are indications of huge domestic infrastructure bottlenecks in countries in Asia. Based on direct and indirect evidence related to trade barriers, this paper concludes that complementary trade policies focusing on price and non-price barriers have immense importance in enhancing international trade and integration in the post-crisis period.